Analisis Nilai Tukar Petani Komoditas Pepaya di Kecamatan Dimembe dan Perbandingannya dengan Nilai Tukar Petani Hortikultura Provinsi Sulawesi Utara - George Gamaliel Pondaag; Maya Hendrietta Montolalu; Theodora Maulina Katiandagho (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2026)
This study aims to analyze the Farmer’s Terms of Trade (FTT) of papaya commodities in Dimembe District and compare it with the horticultural FTT of North Sulawesi Province in 2024. The research was conducted in Matungkas and Laikit villages using a survey method with a quantitative descriptive approach. Primary data were obtained through interviews with 10 papaya farmers selected using purposive sampling, while secondary data were sourced from the Central Bureau of Statistics. The results show that the average FTT of papaya farmers was 178.19, which is higher than the horticultural FTT of North Sulawesi Province at 160.26. This indicates that the welfare level of papaya farmers is relatively better. The high FTT is influenced by higher farm income, stable selling prices, and farmers’ ability to efficiently manage production costs and household expenditures.